The Effect of Intercropping on Soil Structure Attributes and Soil Erosion on Sloping Land - Asbir Sutan Saidi, Adrinal (2002)
Soil erosion problems in Malaysia have been recognized for a long time. However, management of upland area that is more exposed to soil erosion and soil degradation risk through introduction of different cropping systems is still largely unknown. Consequently, the current knowledge of rates of soil loss on upland slopes is very limited. Therefore, the objectives of this study were to evaluate the effect of intercropping on soil structure attributes and soil erosion, and to evaluate effect of slope position on structural attributes and soil erosion. Two experiments of intercropping of banana and pineapple and intercropping of immature rubber with banana and pineapple consisting of standard erosion plot and on farm research respectively were carried out for 40 months. In the first experiment, four standard erosion plots of slopes 9% and length 22.1 m were prepared. Plot sizes were 22.1 x 2.5 m, 22.1 x 5.0 m, 22.1 x 5.0 m, and 22.1 x 2.5 m for bare plot, banana plot, banana-pineapple intercropped plot, and pineapple plot, respectively. In the second experiment a farmer's field of an area 11 ,250 m2 of intercropping was selected. The slope varied from 9-15%. Both experiments focused on evaluating some soil properties that were closely related to soil structure such as bulk density, soil aggregate stability, soil organic matter, runoff, and soil loss. The effect of root biomass on the above properties was also evaluated.